ANALISIS KOMPONEN KIMIA MINYAK KAYU CENDANA DENGAN KROMATOGRAFI GAS - Abdul Hakim Lukman; Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The purpose of this research is to identify chemical components of sandalwood oil by using the gas chromatography method. This sandalwood oil was obtained by steam and water distillation for 18, 24, and 30 hours distilling times. The condition of the gas chromatography employed was adjusted to : injector temperature 200° C. detector temperature 0° C, initial column temperature 140° C, final temperature column 200° C, speed temperature column 5° C/min, with nitrogen gas as carrier, and the using the flame ionization detector system. The identification of the peak components was done by comparing the relative retention time of the peak component with the peak retention time chemical solution standard. The peak area of each components was calculated by normalization method.The results indicated that chemical components of sandalwood oil, which was produced by the steam and water distillation for 18, 24, and 30 hours, include 0.0391, 0.0271, and 0.0313 % of α-pinene; 0.0065, 0.0034, and 0.0027 % of limonene; 0.9147, 0.7799, and 1.0393 % of α-santalene; 2.4375,1.9802, and 2.3474 % of terpineol 4; 1.2184, 0.7922, and 0. 7921 % of β-santalene; 5. 7263, 3.8800, and 3.9335 % of nerolidol; 48.0481, 51.1802. and 50.3507 % of β-santalol; 22.4367, 24.7127, and 24,2864 % of (arnesol, Unidentified component in each distilling time were 19.1727,15.6443, and 17.2166 %. respectively. The β -santalol component occupies the mayor component of sandalwood oil. The amount of this component at each treating condition was 48.0481 % for 18 hours; 51.1802 % for 24 hours; and 50.3507 % for 30 hours. Terpineol-4, nerolidol, β-santalol. and farnesol components constitute the sandalwood oil and is usually calculated as the total santalol.